The life of Helen Suzman: a psychobiographical study - Nel, Carla (University of the Free State, 2013)
Apart from the current upsurge in interest in psychobiographical research, South African psychologists may be further motivated by the country’s recent political history to embark on a study of exceptional lives or significant figures. A renewed focus on antiapartheid activists could be of great value in the current South African context and the process of constructing a narrative of the nation’s troubled past. Helen Suzman (1917-2009) won worldwide recognition for her role as anti-apartheid activist and parliamentary politician. She displayed exceptional resilience under trying and often hostile conditions and became known for her intolerance of injustice and concern for the plight of the disenfranchised. Helen Suzman’s life has not been the subject of any prior psychologically-informed biography. She was selected through purposive sampling as the subject for this psychobiography. The researcher aimed to provide a psychologically driven exploration and description of aspects of her life within its sociohistorical context, through the application of specific psychological approaches to the available biographical data. The two psychological frameworks used in this study were (a) a stage-based dynamic description of psychosocial development (Erikson, 1963, 1997), and (b) a model for holistic wellness within positive psychology (Myers, Sweeney & Witmer, 2000; Sweeney & Witmer, 1991; Witmer & Sweeney, 1992). The primary aim of this study was therefore to explore and describe Helen Suzman’s psychosocial development and her holistic wellness throughout her lifespan. This objective falls within an inductive research approach, and reflects the exploratory-descriptive nature of the study. Two methodological strategies were used in this study. Firstly, Alexander’s model (1988, 1990) was used to organise, extract, prioritise and analyse the data. The indicators of salience helped ensure that all significant pieces of biographical data were carefully considered for analysis. Posing specific questions to the data enabled the researcher to extract units of analysis relevant to the aim of the study. Secondly, the use of conceptual frameworks and matrices enabled the longitudinal exploration, categorisation and description of the stages of psychosocial development and the components of holistic wellness, respectively. The eugraphic focus of both psychological frameworks enabled the researcher to explore aspects of Helen’s life in terms of healthy development and holistic wellness. Findings from this study suggested that Helen Suzman (a) progressed successfully through all psychosocial stages of development and accrued all ego strengths as proposed by Erikson, and (b) achieved a relatively high degree of wellness in all the dimensions and tasks of the holistic wellness model. Findings from both frameworks, furthermore, highlighted the influence of contextual factors on her psychosocial development and holistic wellness. This study contributed to the body of knowledge on Helen Suzman and the psychobiographical approach. It, furthermore, provided a unique platform for demonstrating the value and relevance of the theory of psychosocial development and the holistic wellness model when applied to an individual life. Based on the application of these theories, recommendations are made for future psychobiographical research projects.
Thesis (Ph.D. Psychology)--University of the Free State, 2013
Keywords: Psychobiography; Helen Suzman; Erik Erikson; Thomas Sweeney; Melvin Witmer; Jane Myers; Psychosocial development; Holistic wellness; Neo-Adlerian; Suzman, Helen; Women in politics -- South Africa; Politicians -- South Africa -- Biography